1985
DOI: 10.1172/jci111683
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins in the hyperimmunoglobulin E and recurrent infection (Job's) syndrome. Deficiency of anti-Staphylococcus aureus immunoglobulin A.

Abstract: Patients with the hyperimmunoglobulin E and recurrent infection syndrome (HIE) characteristically have frequent skin and respiratory infections caused by Staphylococcus aureus. We have developed a set of enzyme-linked immunosorbent assays that use whole S. aureus (Wood's strain) immobilized on 0.22-um filters and highly specific, affinity-purified enzyme conjugates of goat anti-human IgE, anti-human IgD, anti-human IgG, anti-human IgA, and anti-human IgM. These reagents were used to determine S. aureus-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 33 publications
6
35
0
2
Order By: Relevance
“…HIES patients have normal levels of anti-S. aureus IgG and modestly elevated levels of anti-S. aureus IgM. Unexpectedly, antistaphylococcal IgA levels are low in HIES patients (74) and total salivary IgA is also reduced. Quinti et al (86), reported high-molecular-weight immune complexes (>900 000 Da) composed of IgG anti-IgE.…”
Section: Disorders Characterized By Excessive Ige Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…HIES patients have normal levels of anti-S. aureus IgG and modestly elevated levels of anti-S. aureus IgM. Unexpectedly, antistaphylococcal IgA levels are low in HIES patients (74) and total salivary IgA is also reduced. Quinti et al (86), reported high-molecular-weight immune complexes (>900 000 Da) composed of IgG anti-IgE.…”
Section: Disorders Characterized By Excessive Ige Productionmentioning
confidence: 95%
“…Many studies have focused on the immune aspects of the disease, such as detection of eosinophilia in blood, sputum, and abscesses (51,69), defective granulocyte chemotaxis (34,35,40,70), abnormal T lymphocyte subsets (51,71), defective antibody production (72)(73)(74)(75), and decreased production of, or responsiveness to, cytokines such as IL-4 and interferon-gamma (IFN-c) (76)(77)(78)(79). Complement levels were normal when studied.…”
Section: Disorders Characterized By Excessive Ige Productionmentioning
confidence: 99%
“…Skeletal manifestations include joint hyperextensibility, short stature, coarse facial features, hypertelorism, osteopenia with fracture susceptibility, craniosynostosis, degenerative joint disease, and failure to shed primary teeth (44)(45)(46)48). Laboratory investigation reveal near-normal levels of IgG, IgA, and IgM, but IgE frequently exceeds 2000 IU/ml (47,(49)(50)(51). Specific IgE to common allergens is often positive, suggesting that at least a component of IgE is Ag driven.…”
Section: Hiesmentioning
confidence: 99%
“…Functional Ab deficiency. Poor specific humoral immune responses have been documented in HIES (45,(49)(50)(51). This resembles B cell STAT3-deficient mice, which do not mount Ag-specific T cell-dependent IgG responses (35).…”
Section: Proposed Mechanisms Underlying Other Clinical Features Of Admentioning
confidence: 99%
See 1 more Smart Citation